Infl uence of orthostatic test on the heart pumping function in athletes with lower extremities motor disorders - L. I. Vakhitov; T. L. Zefirov; I. Kh. Vakhitov (Спортивная медицина: наука и практика, 2020)
Objective: to study the response of heart pumping function (HPF) of athletes with disabilities to an orthostatic test. Materials and methods: 20 wheelchair athletes (21-30 year-old) were examined. Group I are wheelchair basketball players with amputated lower limbs at the level of the upper third of the tibia. II group - athletes with spinal damage and atrophy of lower limbs at the level of Th 12, L1, with compression, partial rupture of spinal cord, lower limbs paralysis, and small pelvic organ functional disorder. We compared the heart rate (HR) and stroke volume (SV). Th e analysis was carried out in two stages: we take measurements in the lying position and within 5 - 20 seconds aft er an active transition from the lying position to the sitting position. Results: In group I, the HR in the lying position was 77.2±1.4 bpm. With the active change of position, the HR increased by 7.3±1.2 bpm (p<0.05) to 84.5±1.8 bpm. Th e HR in group II in the lying position was 71.3±1.8 bpm. Aft er an active position change, it increased to 75.7±2.1 bpm. Th e HR response to the change of body position in group II was 4.4±1.6 bpm (p<0.05), which was 2.9±1.3 bpm less than the HR response to a change of body position in group I (p<0.05). HR decrease within 4 to 12 bpm may indicate a reduced tone of sympathetic part of vegetative nervous system. Th e SV of group I in the lying position was 54.3±1.6 ml. Aft er active transition from lying position to sitting position, the SV decreased to 45.7±1.9 ml (p<0.05). At transition from lying position to sitting position, the SV reaction in athletes with amputated of lower limbs was 8.6±1.4 ml (p<0.05). In wheelchair basketball players with lower limb atrophy, the SV in lying position was 6.8±1.9 ml and decreased by 4,3±1.7 ml at active transition from lying position to sitting position to 57.5±2.1 ml (p<0.05), which diff ers signifi cantly from the reaction of group I by 4.3±1.6 ml (p<0.05). Conclusions: In group I, the diff erence in HR values in an orthostatic test is signifi cantly higher than in group II.